Detection of Human Bocavirus Genotype 1 (HBoV1) in Children with Acute Asthma and Wheezing Attacks - Ri, Chang Guk; Kim, Hyok; Sin, Yong Chan; Pak, Yong Chol; Song, Yong Su; Paek, Sin Hyok; Kim, Ryong Sik (Medical Science Journal for Advance Research, 2025)
Background: The sole pathogenic role of human bocaviruses, which have recently been discovered and known to cause acute respiratory diseases in children, has not yet been completely understood. Objective: To demonstrate the etiological role of Human Bocavirus alone in children with acute asthma and wheezing attacks. Methods: Nasopharyngeal aspirate (NPA) specimens collected from children who were hospitalized with severe acute asthma and wheezing attacks were tested for Human Bocavirus (HBoV) by PCR with specific primers to HBoV. In addition to, DNA sequence analysis and Phylogenetic analysis of the specific HBoV amplicons were performed. Results: In PCR with primers targeting the HBoV VP1/VP2 and NS1 genes, single and very sharp amplication bands of the expected length of 0.57Kb and 0.35Kb revealized from 3 of 6 NPA specimens. DNA sequence analysis and Phylogenetic analysis of the specific amplicons of HBoV VP1/VP2 and NS1 genes revealed that the virus detected by PCR was HBoV genotype 1 with 98.3 99.9% similarity. Conclusions: The obtained result revealed that our study provides strong support that HBoV can cause severe acute asthma and wheezing attacks in children in the absence of viral and bacterial co-infections.